3D product authenticity model for online retail: An invariance analysis - Raed Algharabat; Charles Dennis (International Journal of Business Science & Applied Management (IJBSAM), 2010)
This study investigates the effects of different levels of invariance analysis on three dimensional (3D) product authenticity model (3DPAM) constructs in the e- retailing context. A hypothetical retailer website presents a variety of laptops using 3D product visualisations. The proposed conceptual model achieves acceptable fit and the hypothesised paths are all valid. We empirically investigate the invariance across the subgroups to validate the results of our 3DPAM. We concluded that the 3D product authenticity model construct was invariant for our sample across different gender, level of education and study backgrounds. These findings suggested that all our subgroups conceptualised the 3DPAM similarly. Also the results show some non-invariance results for the structural and latent mean models. The gender group posits a non-invariance latent mean model. Study backgrounds group reveals a non-invariance result for the structural model. These findings allowed us to understand the 3DPAMs validity in the e-retail context. Managerial implications are explained.
Keywords: 650; 3D product authenticity; control; animated colours; value; behavioural intention; invariance analyses